Zależność pomiędzy poziomem kursu złotówki a obrotami towarowymi w polskim handlu zagranicznym - analiza danych empirycznych - Michalczyk, Wawrzyniec (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2006)
To analyze the correlation between exchange rate and foreign trade of Poland, the author used the simple statistical method and the data published by the Polish National Bank. The main conclusion is that although in theory there is a fundamental connection between the changes in exchange rate and the level of export and import, one cannot unequivocally say that such a connection exists in the Polish economy. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1147, s. 257-263